Export activity, specialisation and structural change - Lawless, Martina Anne (Trinity College (Dublin, Ireland). Department of Economics, 2005)
This thesis examines the evolution of Ireland’s manufacturing exports. In particular, it focuses on the changing pattern of specialisation both of products and of destinations. The first two chapters examine specialisation at the aggregate sector level; the second half of the thesis continues the analysis by looking at the experiences of exporting firms, asking which firms become exporters and where they send their exports.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin